The « Closed Shop » Controversy in Postwar Britain - Dion, Gérard (Relations industrielles / Industrial Relations, 1955)
The article reviews the booklet, "The « Closed Shop » Controversy in Postwar Britain," by Jean T. McKelvey. Reprint Series Number 24. Originally published in Industrial and Labor Relations Review, Vol. 7, No. 4, July 1954,.